Executive Dysfunction and Psychological Symptoms in Problematic Social Media Use - Kahya, Yalçın; Ünsal Mavi, Cansu; Hocaoğlu, Çiçek (Addicta: The Turkish Journal on Addictions, 2025)
This study aimed to investigate the relationship between problematic social media use (PSMU), executive functions, depression, anxiety, stress, and sleep quality in a healthy adult population. A total of 174 adults (62.6% female, mean age = 37.19 ± 9.17 years) were recruited online. Participants completed a sociodemographic data form, the Bergen Social Media Addiction Scale (BSMAS), the Executive Function Index (EFI), the Depression Anxiety Stress Scale-21 (DASS-21), and the subjective sleep quality subscale of the Pittsburgh Sleep Quality Index (PSQI). Pearson correlations were conducted. Problematic social media use showed negative associations with executive functioning, particularly with organization (r = −.423, p < .001). In addition, BSMAS scores were positively correlated with depression (r = .354, p < .001), anxiety (r = .217, p < .001), and stress (r = .233, p < .001). The findings indicate that PSMU is strongly linked to executive function and psychological distress. These results highlight the need for interventions targeting cognitive regulation, emotional well-being, and healthy technology use.